2020
DOI: 10.22571/2526-4338258
|View full text |Cite
|
Sign up to set email alerts
|

Papel da inflamação e desregulação neuroendócrina na obesidade

Abstract: A obesidade é uma condição patológica na qual há um aumento do volume do tecido adiposo, esse estado possui etiologia multifatorial e complexa, além de ser fator de risco para algumas doenças, como diabetes mellitus tipo 2 e hipertensão arterial. Esta revisão tem como objetivo abordar os mecanismos inflamatórios e neuroendócrinos envolvidos na obesidade. A pesquisa corresponde a uma revisão de literatura de caráter descritivo, baseada em artigos científicos, livros e periódicos, com os seguintes descritores: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
0
0
1
Order By: Relevance
“…This inflammatory response and the nonspecific stimulation of the immune system can contribute to the onset and progression of obesity-associated complications. [9] Park and colleagues found that obesity can stimulate inflammatory responses and promote tumor development by increasing the secretion of pro-inflammatory cytokines IL-6 and TNF-α. [51] Highfat diet significantly reduces immunological tolerance, resulting in the overproduction of inflammatory mediators, including TNF-α, IL-6, IFN-γ, and IL-1β, while also causing a significant decrease in antiinflammatory molecules such as IL-10 and IL-4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inflammatory response and the nonspecific stimulation of the immune system can contribute to the onset and progression of obesity-associated complications. [9] Park and colleagues found that obesity can stimulate inflammatory responses and promote tumor development by increasing the secretion of pro-inflammatory cytokines IL-6 and TNF-α. [51] Highfat diet significantly reduces immunological tolerance, resulting in the overproduction of inflammatory mediators, including TNF-α, IL-6, IFN-γ, and IL-1β, while also causing a significant decrease in antiinflammatory molecules such as IL-10 and IL-4.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with chronic, low‐grade inflammation in fat tissues, which can exacerbate oxidative stress. [ 9 ] Furthermore, obesity has been linked to impaired DNA repair activities, which are critical cell responses to DNA damage, leading to mutations, DNA breakage accumulation, and genome instability. [ 10 ] Individuals with obesity have been found to have an accumulation of DNA breakage, which is believed to play a role in the development of obesity‐associated disorders, including malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Nas últimas três décadas, a obesidade triplicou no mundo (WHO, 2018), e tornou-se uma epidemia global (Samaras et al, 2019), afetando todas as idades e níveis socioeconômicos (Rocha et al, 2019;Calzerra et al, 2020). No Brasil, 20,3% de adultos encontram-se com obesidade (VIGITEL, 2019), e os valores totais despendidos com comorbidades são 2,1 bilhões de dólares por ano (Souza et al, 2018).…”
Section: Perspectiva Atual Da Obesidadeunclassified